Camphor derivatives in asymmetric synthesis: a synthetic, mechanistic and theoretical study - Lobb, Kevin Alan (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
A series of 3,3-ethylenedioxy-exo- and endo- bornyl esters have been prepared and subjected to Î±-benzylation using lithium diisopropylamide and benzyl bromide. In the exo-series of esters the diastereofacial selectivity of benzylation was found to improve (up to 34% d.e.) as the steric bulk of the O-alkyl group increased, whereas in the endo-series, a surprising decrease in stereoselectivity was observed as the steric bulk increased "“ an observation attributed to flexibility of the metal-coordinated endo-enolate system, compared to the relative rigidity of the exo analogues. The conformational options for each series was explored at the density functional theory level. Reductive cyclization of a range of specially prepared N-carbobenzyloxy-amino acid esters has been shown to afford the corresponding derivatives, contrary to previous reports that the cyclization is limited to the glycine derivative. The cyclization sequence has been explored in detail, and the yield has been shown to be critically dependent on the stereochemistry of the Î±-amino acid moiety. Moreover, it seems that reductive cyclization occurs more readily with the endo- rather than the exo-bornyl N-CBZ-amino acid esters. Molecular modelling of relevant transition states at the DFT levels indicates that L-amino acid-derived systems should cyclize preferably in the exo-series and D-amino acid-derived systems should cyclize preferably in the endo series. Studies of alkylation of an iminolactone system have reported an interesting anomaly - exo-methylation is observed while endo-alkylation predominates for larger alkyl groups. This has been studied in detail at the DFT level, and the anomaly is attributed to thermodynamic control in the methyl case, whereas kinetic control is the norm in this system. Preliminary computer modelling of the intramolecular rearrangement of a 3,3-xylylbornyl system at the HF/STO-3G level raised doubts concerning the structure assigned by Evans to one of the rearrangement products, prompting an X-ray crystallographic analysis and leading to the revision of its structure from a pinene to a camphene derivative. The previously elusive spiro[bornane-3,2'-indan]-2-exo-tosylate has been successfully isolated, and the kinetics of its ready decomposition to the two camphene products has been followed by 1H NMR spectroscopy. The endo-tosylate analogue, on the other hand, was found to be remarkably stable. Kinetic data obtained for rearrangement of this exo-bornyl tosylate have indicated the operation of tandem autocatalytic and pseudo-first-order transformations leading sequentially to the two isomeric camphene products. An extensive coset analysis of all possible rearrangement processes of the initially-formed cation formed from decomposition of the exo-tosylate has afforded a graph containing 336 classical cations (modelled at the AM1 and B3LYP levels) and 526 transition-state complexes (modelled at the AM1 level). This analysis afforded a viable 4-step classical mechanism connecting the first camphene product with the second. A more realistic study, involving non-classical carbocations, has afforded a graph of all possible (classical and non-classical) cations that could be formed by rearrangment of the initiallyformed cation. The resulting graph confirms that the only energetically feasible path corresponds to the classical mechanism, but simply involves two steps, including a novel, concerted Wagner-Meerwein "“ 6,2-hydride shift "“ Wagner-Meerwein rearrangement.
Keywords: Chemistry, Organic -- Research; Esters; Organic compounds -- Synthesis; Alkylation; Chemical reactions -- Computer simulation; Chemical kinetics; Camphor; Cinnamomum